Effective problem solving in suicide attempters depends on specific autobiographical recall. - Pollock, L; Williams, J (2001)
The relationship between over-general autobiographical memory and interpersonal problem solving was investigated by comparing a group of suicide attempters with a nonsuicidal psychiatric control group and a normal control group. Results showed that suicide attempters were more over-general in memory and displayed significantly poorer problem solving than the other two groups. Furthermore, suicide attempters who were more over-general displayed greater deficits in problem solving. It was concluded that effective problem solving in suicide attempters depends on specific autobiographical recall.